Integrated approach for the eco design of a new process through the life cycle analysis of olive oil: Total use of olive by‐products. Issue 9 (3rd April 2017) - Guermazi, Zina; Gharsallaoui, Mariem; Perri, Enzo; Gabsi, Slimane; Benincasa, Cinzia
Abstract : The disposal of waste is one of the main problems faced by the majority of the olive growing agribusiness: olive oil by‐products require specific management. In this work, the result of life cycle analysis shows that the major problem is related to the management of mill waste water. The formation of compost from the depleted pomace is bound to the emission of greenhouse gases. Therefore, the traditional way of waste recovery is no longer the best alternative. In this context, we propose a complete process for total use of olive by‐products during the process of olive oil extraction. The project presents a pulp olive oil rich in natural antioxidants, stone olive oil for cosmetic application and an olive paste with a smoky taste for food consumption. The proposed system contributes to lower the environmental impact, improve the quality of the oil, and promote the development of new and useful by‐products. Practical applications: A new facility composed of a destoner and a two phase extraction system is proposed to improve the working capacity and contribute to lower the environmental impact during all the process of olive oil production. The proposed new system produces, on the one hand, an olive pulp that gives an extra virgin olive oil rich in natural antioxidants and an olive paste with a smoky taste for food consumption, and on the other hand, stones that gives an olive oil for cosmetic application and a raw material to produce energy. Life cycle analysis of olive oil is used as a tool to design a new production process in olive growing agribusiness for cleaner production. The new facility, composed of a destoner and a two phase extraction system, improves the working capacity and contributes to lower the environmental impact. It produces an olive pulp that gives, on the one hand, an extra virgin olive oil rich in natural antioxidants and an olive paste with a smoky taste for food consumption, and, on the other hand, stones that gives an olive oil for cosmetic application and raw material for producing energy. Abstract : Life cycle analysis of olive oil is used as a tool to design a new production process in olive growing agribusiness for cleaner production. The new facility, composed of a destoner and a two phase extraction system, improves the working capacity and contributes to lower the environmental impact. It produces an olive pulp that gives, on the one hand, an extra virgin olive oil rich in natural antioxidants and an olive paste with a smoky taste for food consumption, and, on the other hand, stones that gives an olive oil for cosmetic application and raw material for producing energy.